Ochrona środowiska naturalnego przez międzynarodowe prawo karne - Krzan, Bartłomiej (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article’s goal is to determine the relevance of international criminal law for the protection of environment. It examines the potential enforcement of international environmental law by bringing perpetrators of violations to international criminal responsibility. The analysis thus touches upon fundamental issues of what an international crime is, who may commit it and to what extent it may be subject to punishment. Furthermore, it discusses the extension of the jurisdiction of the ICC to cover acts harmful to the natural environment, also by accommodating environmental concerns into the existing treaty-framework. From a more general perspective, the analysis offers a critical examination of the overlap or convergence between environmental protection goals and contemporary international criminal law, also giving expression to the actual condition of international cooperation in both these areas.
Keywords: międzynarodowe prawo karne; prawo ochrony środowiska; środowisko naturalne; zbrodnie międzynarodowe; przestępstwa przeciwko środowisku; ekocyd; Międzynarodowy Trybunał Karny